Sex differences in circulating leptin as a marker of adiposity in obese or overweight adolescents with type 1 diabetes. Issue 1 (21st October 2020) - Redondo, Maria J; Siller, Alejandro F; Gu, Xiangjun; Tosur, Mustafa; Bondy, Melissa; Devaraj, Sridevi; Sisley, Stephanie
Abstract : Introduction: We aimed to test whether the serum adipokines leptin and adiponectin are more strongly associated with body fat percentage (BF%) than body mass index (BMI) in adolescents with type 1 diabetes (T1D) and overweight/obesity. Research design and methods: We studied all participants in the T1D Exchange Metformin Study (n=122, median age 12.9 years, range 12–19.5; 32% males; 77% non-Hispanic whites, 100% overweight or obesity; median diabetes duration 6.7 years, range 1.4–15) with a baseline serum sample where we measured leptin and adiponectin concentrations. Anthropometric, clinical, laboratory and dual-energy X-ray absorptiometry (DEXA) scan measurements were analyzed. We compared correlation coefficients between variables of interest. Results: BF% by DEXA was significantly correlated with BMI Z-score (r=0.38, p<0.0001), BMI per cent of the 95th percentile (BMI%95) (r=0.45, p<0.0001), waist circumference (r=0.46, p<0.0001), leptin (r=0.58, p<0.00001) and leptin/adiponectin ratio (r=0.36, p<0.0001), while it was not significantly correlated with absolute body weight, adiponectin or insulin dose (total or basal). BF% was significantly more strongly correlated with leptin than with BMI Z-score in the overall group (p=0.022). However, there were sex-based differences. Among the significant correlations in the overall group, BF% was most strongly associated with leptin (r=0.75) in boys (n=39) but with waist circumference (r=0.58) in girls (n=83) (all p<0.0001). Conclusions: Serum leptin could be used as a surrogate convenient marker of adiposity in overweight/obese adolescent boys with T1D, equivalent to BMI Z-score or BMI%95. In girls, waist circumference was the best performing marker overall, and was also strongly correlated with %BF in boys.